2022
DOI: 10.1021/acs.chemrestox.2c00268
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette Flavors, Sensory Perception, and Evoked Responses

Abstract: The chemosensory experiences evoked by flavors encompass a number of unique sensations that include olfactory stimuli (smell), gustatory stimuli (taste, i.e., salty, sweet, sour, bitter, and umami (also known as “savoriness”)), and chemesthesis (touch). As such, the responses evoked by flavors are complex and, as briefly stated above, involve multiple perceptive mechanisms. The practice of adding flavorings to tobacco products dates back to the 17th century but is likely much older. More recently, the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 224 publications
0
3
0
Order By: Relevance
“…Flavors in ECIGs evoke chemosensory experiences that has been associated with initiation, progression and dependence or addiction to ECIGs products among youth, young adults, and never smokers [ 47 , 48 ]. Flavors enhance the palatability of high concentrations of ECIGs constituents, such as nicotine, PG and VG [ 15 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavors in ECIGs evoke chemosensory experiences that has been associated with initiation, progression and dependence or addiction to ECIGs products among youth, young adults, and never smokers [ 47 , 48 ]. Flavors enhance the palatability of high concentrations of ECIGs constituents, such as nicotine, PG and VG [ 15 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the appeal and prevalence of EC among youth are usually attributed to several factors including flavoring, customizability, and effective nicotine delivery [5][6][7][8][9][10]. While there is strong reason to believe that flavors contribute to EC appeal in youth, [11][12][13] sustained use could be attributed to efficient nicotine delivery [14]. Early EC devices (i.e., cig-a-like) were flavored yet delivered little or no nicotine to the user and their use was not sustained [15].…”
Section: Background and Rationalementioning
confidence: 99%
“…Reportedly, there are ∼17,000 flavored e-liquid products available on the market from over 450 retail brands. These flavors can be grouped into 12 categories, i.e., tobacco, menthol/mint, nuts, spices, coffee/tea, alcohol, other beverages, fruit, dessert, candy, other sweets, and others . Although most of the flavoring chemicals used in e-liquids are considered safe for ingestion by the Flavors and Extract Manufacturers Association (FEMA), this assessment is not necessarily valid for inhalation. In accordance with flavor variety and attractiveness among youth, there has been a vast emergence of research on the pulmonary toxicity of e-cigarette flavors. A collection of in vitro studies have identified a dose-dependent toxicological effect of common flavoring ingredients used in commercial e-liquids, including maltol, ethyl maltol, vanillin, and cinnamaldehyde, on human respiratory cells. Likewise, benzaldehyde is a primary ingredient in many cherry flavored e-liquids, yet it is a known respiratory irritant with potential to cause acute lung injury. , Studies have also found flavored e-liquids to produce reactive oxygen species (ROS) when vaporized, which can impair blood vessels, thus increasing the risk of developing cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%